Computer and internet interventions to optimize listening and learning for people with hearing loss: accessibility, use, and adherence - Ferguson, Melanie A.; Henshaw, Helen (ASHA, 2015)
Purpose: The aim of this research forum article was to examine accessibility, use, and adherence to computerized and online interventions for people with hearing loss. Method: Four intervention studies of people with hearing loss were examined: 2 auditory training studies, 1 working memory training study, and 1 study of multimedia educational support. Results: A small proportion (approximately 15%) of participants had never used a computer, which may be a barrier to the accessibility of computer and Internet based interventions. Computer competence was not a factor in intervention use or adherence. Computer skills and Internet access influenced participant preference for the delivery method of the multimedia educational support program. Conclusions: It is important to be aware of current barriers to computer and Internet-delivered interventions for people with hearing loss. However, there is a clear need to develop and future-proof hearing-related applications for online delivery.